Study on compact polarized light beam splitting system for generating sodium guidestars constellation. (February 2022) - Bian, Qi; Bo, Yong; Zuo, Jun-Wei; Peng, Qin-Jun
Highlights: Beam splitting system is key for multi-conjugate adaptive optics telescope. A simple and compact polarized light beam splitting system is developed. A polarizer and a reflector is creatively synthesized to be one mirror. One incident beam is split into four beamlets within only 0.002 m 2 work area. This approach opens up a new way to generate sodium guidestars constellation. Abstract: A simple and compact polarized light beam splitting system is developed to split one sodium laser beam into multiple beamlets. Here, a polarizing beam splitter and a high reflection mirror is creatively synthesized to be one mirror as the special splitter-and-coupler, whose operation principle is introduced in detail. A Jones matrix model is utilized for theoretical analysis of the amplitude variation and energy distribution of the splitting beamlets. As a result, four yellow beamlets with the power ratio of 1:1:1:1 and orthogonally linearly polarized state are achieved within only 0.002 m 2 working area. This approach opens up a new way to generate sodium guidestars constellation for the extended-field-of-view multi-conjugate adaptive optics telescopes.